Mining Students’ Feedback in a General Education Course: Basis for Improving Blended Learning Implementation - Celestial-Valderama, Arlene Mae; Vinluan, Albert; Moraga, Shirley D. (International Journal of Computing Sciences Research; Vol 5 (2021): Vol 5, 2021)
Purpose – The role of student feedback is paramount in the continuous improvement cycle in teaching and learning.  The same applies to academic institutions implementing traditional face-to-face, blended, and fully online learning who leverage feedback analysis as an underlying and powerful approach in its construction of design in quality, efficiency, and effectiveness.  In this paper, the acquisitions of feedback from students quantifiably and qualitatively such as mining of actual comments are the primary source of data.  The study unravels the research question of how unstructured students’ feedback be mined to prescribe course improvements in a blended learning course. Method – An analysis of the students' responses who have mostly "strongly disagreed" from their Learning Management System experience survey is achieved statistically via bottom box scoring.  These courses stem from a roster of blended learning programs offered at Jose Rizal University.  From this exacting general education course, a qualitative text mining approach comprising of text pre-processing, topic extraction, sentiment analysis, and data visualization using actual student comments are probed. Results – The Canvas LMS experience survey ensued HIS C101, a general education course identified with the most responses of students’ strong disagreement.  The study prescribes the employment of a feedback mining process which presents the results of the text mining approach from the qualitative comments from HIS C101 learners that seemingly resolves in the formation of recommendatory action plans aiming the improvement of the blended learning implementation.   Conclusion – With the feedback mining process in place, it serves as a channel and basis for improving the blended learning experience of the students. Recommendations – More so to gather a more profound indulgence to expedite the university stakeholders in course improvement cycles in the other courses offered and included in the blended learning programs of the university. Research Implications – Learner criticism is invariably considered vital if an institution has constant methods in the improvement cycle on how they implement the teaching and learning process.  Any improvement in the cycle must take the client's feedback as input and thus converted it into definite action plans.  This research is timely and immutable as diverse modes have come across the practices of teaching and learning in the world at large.